2014
DOI: 10.1186/2192-1709-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing hydrological and provisioning ecosystem services in a case study in Western Central Brazil

Abstract: Introduction: Current land use in the Federal District, Western Central Brazil, causes problems related to the water supply which are linked to the regulation of ecosystem services (ES). In scope of an Integrated Water Resources Management concept, we further developed the web-based planning support tool GISCAME for the Pipiripau river basin case study. Methods: We introduced analyses on ecosystem potentials in the raster-based tool to assess, in a spatially explicit manner, the scenario impact on water purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…Many of the benefits that humans gain from ecosystems are directly or indirectly related to freshwater, which are referred to as water related ecosystem services (Koschke et al, 2014), but little attention has been paid to the potential loss of ecosystem services (ES) due to water stress (Qin et al, 2014). Water is usually the single most important limiting factor for the growth and productivity of plants (Inman-Bamber et al, 2012;Nielsen, 2003), and many areas worldwide have been facing increasingly severe water scarcity (De Fraiture et al, 2008;Zhang and Xia, 2009), especially the arid and semi-arid regions that are very sensitive to climate change and human activities (Rockström and Gordon, 2001;Saue and Kadaja, 2014;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the benefits that humans gain from ecosystems are directly or indirectly related to freshwater, which are referred to as water related ecosystem services (Koschke et al, 2014), but little attention has been paid to the potential loss of ecosystem services (ES) due to water stress (Qin et al, 2014). Water is usually the single most important limiting factor for the growth and productivity of plants (Inman-Bamber et al, 2012;Nielsen, 2003), and many areas worldwide have been facing increasingly severe water scarcity (De Fraiture et al, 2008;Zhang and Xia, 2009), especially the arid and semi-arid regions that are very sensitive to climate change and human activities (Rockström and Gordon, 2001;Saue and Kadaja, 2014;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding hydrological services, LULC change is one of the most significant anthropogenic pressures which change water flows and modify regulating hydrological services [10] [27] [28]. In addition, slope, topography, soil development and soil depth are also terrestrial characteristics of the watersheds which impact hydrologic services, as reported by [29] [30], among others.…”
Section: Methodsmentioning
confidence: 99%
“…Though many studies have been performed to describe and model the relations between LULCC and hydrological functions and services, understanding and predicting the impact of changes at different scales is still not suffi ciently solved to serve planning and management at the regional to local scale where most LULCC decisions are made (see e.g. Koschke et al 2014 ). A challenge consists in refi ning the scale where interrelations between hydrological functions and services and LULCC are modeled: the assessment of LULCC focuses mainly on land-cover classes and ignores the variability of land-use and management alternatives (Van Oudenhoven et al 2012 ;Verburg et al 2009 ;Dale and Polasky 2007 ).…”
Section: Challenges For Assessing the Impact Of Land-use Changes On Hmentioning
confidence: 99%